2020
DOI: 10.3389/fmed.2020.579603
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Microangiopathy and Acute Kidney Injury Induced After Intravitreal Injection of Vascular Endothelial Growth Factor Inhibitors VEGF Blockade-Related TMA After Intravitreal Use

Abstract: Vascular endothelial growth factor (VEGF) inhibition can cause worsening hypertension, proteinuria, chronic kidney injury, and glomerular disease. Thrombotic microangiopathy (TMA) and other nephrotic disorders have been reported with systemic VEGF blockade. These same agents are given intravitreally for age-related macular degeneration (AMD) and diabetic retinopathy (DR), albeit at lower doses than those given for systemic indications. Systemic absorption of anti-VEGF agents when given intravitreally has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
0
28
0
1
Order By: Relevance
“…CD27 and increased expression of CXCL13 may support blast response from B cells, as is seen in COVID-19, further propelling vascular inflammation and lung injury (57). This inflammatory process is further fueled by significant activation of the VEGF activation pathways, as seen in our dataset (58). Together with CD27 and TWEAK activation, this is highly suggestive of ongoing vasculitis, a common feature of organ dysfunction in COVID-19 (51,59,60).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…CD27 and increased expression of CXCL13 may support blast response from B cells, as is seen in COVID-19, further propelling vascular inflammation and lung injury (57). This inflammatory process is further fueled by significant activation of the VEGF activation pathways, as seen in our dataset (58). Together with CD27 and TWEAK activation, this is highly suggestive of ongoing vasculitis, a common feature of organ dysfunction in COVID-19 (51,59,60).…”
Section: Discussionmentioning
confidence: 57%
“…The only advent of kidney failure, liver failure, and need for pressors was associated with elevation of specific markers (CCL4, CD40, CXCL5, and IL-15), but our findings' interpretation needs more broad context (66). Elevation in VEGFA and CD28 in patients with kidney failure suggests its involvement in the emergence of this organ failure (58,67). Similarly to the lungs, the observed inflammatory profile suggests an environment where T cells and NK are activated.…”
Section: Discussionmentioning
confidence: 59%
“…A recent study reported that intravitreal injection of bevacizumab triggers TMA-like lesions in glomeruli, causing proteinuria 21,22,23 . From these findings, clinicians should be aware that even the local use of bevacizumab, such as via intravitreal injection, can lead to a systemic side effect, although the possibility is supposedly negligible.…”
Section: Drug-induced Renal Complicationsmentioning
confidence: 99%
“…Также вероятно постепенное снижение почечной функции вплоть до терминальной стадии [9,10]. Кроме того, возможно снижение скорости клубочковой фильтрации (СКФ) вплоть до развития острого почечного повреждения даже при интравитреальном введении [11,12]. Определение биомаркеров, которые позволили бы распознавать процессы ишемии почечного интерстиция и повреждение клубочков на ранних стадиях, может способствовать снижению риска развития почечной дисфункции при оптимизации лечения и сопутствующей терапии.…”
Section: Introductionunclassified